2008
DOI: 10.1159/000135670
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Dental Caries among Professional Truck Drivers in Mexico

Abstract: Background: Professional truck drivers are at high risk of chronic diseases. Further examination of tobacco use and its impact on oral health is warranted – both in terms of the direct association between tobacco use and poor oral health, and in terms of tobacco use being an indicator of poor health behaviors. Objective: To estimate the possible association between smoking and dental caries experience in a population with high tobacco use. Methods: Drivers’ licenses are periodically re-issued by the Mexican go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
2
27
0
3
Order By: Relevance
“…Few studies [Axelsson et al, 1998] showed a positive association between caries experience and smoking, without reporting the exact rule of the association. While acknowledging that a large number of missing teeth were due to periodontal disease [Sgan-Cohen et al, 2000;Röthlisberger et al, 2007], it is reasonable to assign responsibility for some of these missing teeth to caries [Aguilar-Zinser et al, 2008]. In the present study the M (missing teeth due to caries) component of DMFS was similar in heavy smokers, light smokers and non-smokers.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Few studies [Axelsson et al, 1998] showed a positive association between caries experience and smoking, without reporting the exact rule of the association. While acknowledging that a large number of missing teeth were due to periodontal disease [Sgan-Cohen et al, 2000;Röthlisberger et al, 2007], it is reasonable to assign responsibility for some of these missing teeth to caries [Aguilar-Zinser et al, 2008]. In the present study the M (missing teeth due to caries) component of DMFS was similar in heavy smokers, light smokers and non-smokers.…”
Section: Discussionsupporting
confidence: 42%
“…Recently, an association between dental caries and smoking habit has been reported [Aguilar-Zinser et al, 2008;Al-Habashneh et al, 2009], suggesting that smoking has an adverse effect on oral health, both in clinical periodontal parameters and caries risk. Tobacco use could have a role in changes of the bacterial ecology and plaque accumulation [Pihlstrom et al, 2005].…”
mentioning
confidence: 99%
“…Finally, five studies of dental caries (n = 4) [27][28][29][30] and oral bacteria (n = 1) [31] were included in the qualitative analysis. One of the included studies also described a relationship between tobacco smoking and salivary secretion rate.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies referred to sub-groups of a population: the Italian Military Academy and professional truck and bus drivers in Mexico [27,29]. The other two described tobacco effects in wider populations: the Rakai District in south-western Uganda [28] and the County of Värmland in Sweden [30].…”
Section: Dental Cariesmentioning
confidence: 99%
“…Along with lung cancer, vascular stenosis, heart attacks and periodontal disease, dental caries has been reported to be associated with smoking all over the world, including Swedish and US smokers, Mexican truck drivers, Turkey and Japanese children, and Italy military personnel (4)(5)(6)(7)(8)(9). A recent study in Japan demonstrated smokers received more caries/endodontic treatment than non-smokers (10).…”
Section: Introductionmentioning
confidence: 99%